Inactivation of Fungi in Treated Surface Water by Chloramination. Issue 1 (1st January 2017) - Pereira, Vanessa J.; Marques, Marta; Marques, Rosalina; Benoliel, Maria J.; Barreto Crespo, Maria T
Abstract : This study evaluated the efficacy of chloramination to inactivate fungi isolates ( Aspergillus fumigatus, Aspergillus terreus, Cladosporium tenuissimum, Penicillium citrinum, and Phoma glomerata ) reported to occur in drinking water sources with different compositions. Inactivation rate constants were determined for laboratory‐grade water and real treated surface water samples, with higher rate constants than are often reported in laboratory‐grade water. The effects of conducting disinfection at different temperatures were also evaluated. Results showed that the Penicillium and Aspergillus species tested were more resistant to inactivation using chloramines than were the Cladosporium and Phoma species. Higher inactivation levels were observed at higher temperatures, especially for the Cladosporium and Phoma species tested. The degree of sensitivity of fungi to chloramination varied among the different genera. Water treatment plants applying chloramination can expect inactivation efficiency similar to free chlorine for most of the selected fungi isolates tested.